Variability of the Chromatin Decondensation Ability Test on Human Sperm - Huret, J. L. (Archives of andrology, 1983)
A sperm nuclear decondensation ability test using 1% SDS + 6 mM EDTA was used to evaluate: a system of classification and nomenclature for the decondensation of nuclear chromatin; the progress of decondensation as a function of the duration of exposure to SDS/EDTA; the residual variance, or "scoring error;" the within-subject variance (N = 5); and the between-subject variance (N = 10). The process of chromatin decondensation was found to be a continuous phenomenon, but a scheme of nomenclature using four categories along with a system of data analysis using class weightings were developed. A 5-min exposure to SDS/EDTA resulted in a minimum scoring error (8.34%). The within- and between-subject variances were not significantly different from each other, but both were individually different (p < 0.001) from the residual variance.